2019
DOI: 10.21451/1984-3143-ar2018-0147
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycobacterium avium subsp. paratuberculosis in reproductive tissue and semen of naturally infected rams

Abstract: Mycobacterium avium subsp. paratuberculosis (MAP) is the causative agent of paratuberculosis (PTB), disease that causes a syndrome of bad nutrient absorption, weight loss and eventually death. The intestine is the main target organ where the infection develops; however, there is evidence of infection by MAP in extra-intestine sites of sheep, including mesenteric nodes and semen. The aim of the study was to identify the presence of MAP in reproductive tissue and semen of infected Pelibuey rams in clinical state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…However, humoral immunity due to MAP positivity was notable in the summer (MELISA). As a study on the detection of MAP in reproductive tissue showed that horizontal sex transmission increases the risk of MAP dissemination in infected rams, even though the lesions related to Johne’s disease are not developed in the reproductive tissues, MAP can be disseminated to the reproductive tissues [ 37 , 38 , 39 , 40 , 41 , 42 ]. Also, an Italian study on MAP seroprevalence in dairy sheep flocks evidenced that the rate of MAP seropositivity was enhanced in the spring and autumn ( p < 0.071) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, humoral immunity due to MAP positivity was notable in the summer (MELISA). As a study on the detection of MAP in reproductive tissue showed that horizontal sex transmission increases the risk of MAP dissemination in infected rams, even though the lesions related to Johne’s disease are not developed in the reproductive tissues, MAP can be disseminated to the reproductive tissues [ 37 , 38 , 39 , 40 , 41 , 42 ]. Also, an Italian study on MAP seroprevalence in dairy sheep flocks evidenced that the rate of MAP seropositivity was enhanced in the spring and autumn ( p < 0.071) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%